KSHV requires vCyclin to overcome replicative senescence in primary human lymphatic endothelial cells. - Terri A DiMaio; Daniel T Vogt; Michael Lagunoff (PLoS Pathogens)
Kaposi's Sarcoma Herpesvirus (KSHV) is present in the main tumor cells of Kaposi's Sarcoma (KS), the spindle cells, which are of endothelial origin. KSHV is also associated with two B-cell lymphomas, Primary Effusion Lymphoma (PEL) and Multicentric Castleman's Disease. In KS and PEL, KSHV is primarily latent in the infected cells, expressing only a few genes. Although KSHV infection is required for KS and PEL, it is unclear how latent gene expression contributes to their formation. Proliferation of cancer cells occurs despite multiple checkpoints intended to prevent dysregulated cell growth. The first of these checkpoints, caused by shortening of telomeres, results in replicative senescence, where cells are metabolically active, but no longer divide. We found that human dermal lymphatic endothelial cells (LECs) are more susceptible to KSHV infection than their blood-specific endothelial cell counterparts and maintain KSHV latency to higher levels during passage. Importantly, KSHV infection of human LECs but not human BECs promotes their continued proliferation beyond this first checkpoint of replicative senescence. The latently expressed viral cyclin homolog is essential for KSHV-induced bypass of senescence in LECs. These data suggest that LECs may be an important reservoir for KSHV infection and may play a role during KS tumor development and that the viral cyclin is a critical oncogene for this process.